Firearm Ownership, Defensive Gun Usage, and Support for Gun Control: Does Knowledge Matter? - Kruis, Nathan E. (American journal of criminal justice, 2023)
Recent incidents of gun violence have raised questions about public access to "military-style" firearms and the need for more-restrictive forms of gun control. Proponents of more-restrictive forms of gun regulation argue that such measures will help combat the disproportionately high rates of gun crime in the United States. Opponents believe that such measures infringe upon constitutional rights and hinder law-abiding citizens' abilities to adequately defend themselves. This project explores the characteristics of gun owners living in Pennsylvania and public perceptions of three different categories of gun control. Results indicate that most gun owners have received some form of training and take appropriate safety precautions with their firearms. Further, 1 in 4 gun owners reported using their firearm in self-defense at some point in their life. Regarding gun control, most participants favored strategies intended to keep guns away from dangerous and "at risk" people, such as required background checks for all types of gun purchases, mental health screenings, and mandatory gun education. However, most participants opposed complete firearm bans. Among those who are the least supportive of such polices are those who are the most knowledgeable about gun crime, gun legislation, and gun functioning. Policy implications are discussed within.